Character induction in p-groups - Teresa L. Santa Coloma (International Journal of Mathematics and Mathematical Sciences)
Let G be a finite p-group and let χ be an irreducible character of G. Then χ is monomial; that is, χ=λG, where λ is a linear character of some subgroup of G. We are interested in locating subgroups of G which induce the character χ.